Making bioreceptive concrete: Formulation and testing of bioreceptive concrete mixtures. (December 2021) - Veeger, M.; Ottelé, M.; Prieto, A.
Abstract: Increased urbanisation will put an increasing strain on our green spaces, which is expected to have a significant effect on our physical and mental health, as well as the health of our ecosystems. As such it is important to integrate more green spaces in our urban fabric. One way of doing this is by making use of so-called bioreceptive concrete on our façades and other structures, which allows for biological growth to take place on the concrete substrate itself, without requiring any additional systems or maintenance. However, the challenge is to create an affordable concrete mixture that is sufficiently bioreceptive for biological growth to take place. As such, in our research we test four possible measures to make concrete more bioreceptive: changing the aggregate to CEC (crushed expanded clay), adding bone ash to the mixture, increasing the wcf (water cement factor) and using a surface retarder on the concrete. Of these measures, changing the aggregate to CEC (p = 0.024), the addition of bone ash (p = 0.022) and the use of a surface retarder (p < 0.001) were found to significantly increase bioreceptivity. Increasing the wcf factor, however, was not found to significantly increase bioreceptivity (p = 0.429). It was also found that whereas it was previously though a pH below 10 is necessary for biological growth to take place, this does not appear to be the case. Although further research under natural conditions is necessary, the creation of an inexpensive bioreceptive concrete looks to be feasible. Graphical abstract: Image 1 Highlights: Recently a new type of green building material has been touted in the form of bioreceptive materials. Stimulate moss growth on building materials in order to improve urban climate and increased wellbeing of people in houses. Bioreceptive materials to be used as a façade cladding generates a new building perspective. It is likely not necessary to create concrete with a pH below 10 to support extensive biological growth.